Performing the real and terrifying domestic crisis in Martin McDonagh’s The beauty queen of leenane - Peña Puebla, Esther de la (Epos : Revista de filología, 2012)
Martin McDonagh’s The Beauty Queen of Leenane portrays a brutal domestic crisis between mother and daughter in an Irish rural household set in Connemara. The raging dissensions in their relationship emerge as a consequence of the load of religious tradition, deep-seated generic mores, and liminal nationalistic ambiguities. The blatant «in-yer-face » drama Maureen incarnates revolves against her fragile hopes for personal realization, and her mother’s fight for control. Furthermore, Maureen’s frustration and anxiety are deeply intensified by her claustrophobic, murky environment. Thus, McDonagh´s contemporary Irish identity distills a strong sense of entropy which struggles to redefine itself through an interwoven, post-colonial Irish heritage, traced by internal strife, diaspora and exile. Ultimately, what is unique to McDonagh’s play is his pessimistic voice offering no solution for a better future. His clear, honest and provocative testimony speaks of awareness of the Irish history and its dramatic consequences in the present. La obra de Martin McDonagh The Beauty Queen of Leenane (La reina de belleza de Leenane) escenifica una brutal crisis doméstica entre madre e hija en una casa familiar irlandesa, situada en la región de Connemara. Las violentas confrontaciones que salpican la convivencia de ambas mujeres surgen como resultado de una tradición religiosa y social arraigada, con un trasfondo liminal nacionalista ambiguo e indeterminado. Perteneciente al denominado teatro «in-yer-face», la protagonista del cruento drama, Maureen, se enfrenta al conflicto que emana entre sus frágiles aspiraciones personales y el férreo control que ejerce su madre sobre su vida. La frustración y ansiedad que padece Maureen se ven incrementadas, adicionalmente, por el entorno doméstico claustrofóbico y lóbrego en el que discurre su vida. Así, McDonagh consigue transmitir la entropía existencial que destila la identidad irlandesa contemporánea, que lucha por redefinirse a través de un complejo legado postcolonial, marcado por los conflictos internos, la diáspora y el desarraigo. Finalmente, la originalidad de McDonagh recae en su propia voz, honesta, pesimista y carente de esperanza. Su testimonio, provocador y lacerante, habla de la conciencia histórica irlandesa, y sus dramáticas consecuencias en el presente.